Progress in DNP theory and hardware - Van der Drift, Anniek (2012)
Dynamic nuclear polarisation is a technique that allows one to increase the signal-to-noise ratio in an NMR experiment substantially, by transferring the inherently larger electron polarisation to the nuclei. Quantum mechanical models of this effect have thus far been limited to the description of only a few nuclei. This is due to the exponential scaling of the matrices involved in the description of the system. In this thesis methods of reducing the state space needed to accurately describe the simulation of solid effect DNP were explored and tested. Krylov Bogoliubov averaging has been used to remove high frequency oscillations from the system Hamiltonian and confine the trajectory of the dynamics to the zero quantum coherence subspace. Truncation of the basis spanning the Liouville space to low spin correlation orders has been tested and a condition for a minimum truncation level was found. A strategy based on a projection method, which allows one to describe the spin polarisation transient with multi-exponential functions, is introduced. This results in a linear scaling of the propagator with the number of spins. The influence of the parameters involved in the solid effect on the dynamics of the polarisation build up is discussed.